Fibre-Optic Dosimetry for MRI-LINACs: A Mini-Review - Madden, Levi; Holloway, Lois; Rosenfeld, Anatoly; Li, Enbang (Frontiers in Physics, 2022)
For the past few decades, fibre-optic dosimeters (FODs) have been a focus of research for dosimetry with LINACs, owing to a unique set of advantageous qualities: compact dosimeter sizes, an all optical composition (i.e. no wires or electronics around their sensitive volume), real-time response proportional to the absorbed dose-rate in their sensitive volumes and direct water equivalence. Such a set of qualities makes FODs "near-correctionless" for dosimetry with LINACs, such that they have been recommended as in vivo dosimeters and small field dosimeters. Further, their scintillation and luminescence response mechanisms are not affected by magnetic fields. Given this set of qualities, FODs are attractive candidates for dosimetry with MRI-LINACs. This mini-review aims to provide an overview of FODs to the wider medical physics community, and present the current challenges and opportunities for FODs given previous investigations into MRI-LINAC dosimetry.